Identification and mapping of QTLs for late blight resistance in the wild tomato (Solanum pimpinellifolium) accession PI 270442 via selective genotyping - Sullenberger, Matthew T.; Foolad, Majid R. (Frontiers in Plant Science, 2024)
Late blight (LB), caused by the oomycete Phytophthora infestans, is one of the most devastating diseases of the cultivated tomato (Solanum lycopersicum) worldwide. Attempts to control the disease through fungicide applications are becoming less effective, as new and aggressive genotypes of the pathogen emerge. Further, some new P. infestans genotypes overcome the currently available resistance in tomato, necessitating the identification, characterization, and utilization of new sources of host resistance. In the present study, to detect QTLs underlying LB resistance in a recently-identified LB-resistant S. pimpinellifolium accession (PI 270442), an F2 population (n = 1,175) of a cross between PI 270442 and LB-susceptible tomato breeding line Fla. 8059 was screened for LB resistance and subjected to selective genotyping. A total of 19,839 single-nucleotide polymorphisms (SNPs) were identified from reduced representation libraries (RRLs) constructed from the parents, of which 212 were used to build a genetic linkage map and locate QTLs. Ten LB-resistance QTLs were identified in PI 270442 on chromosomes 1, 2, 5, 6, 10, 11 and 12, of which those on chromosomes 6, 10 and 11 were the strongest and co-localized with previously-reported LB-resistance QTLs. Genomic locations of the QTLs were compared with the tomato physical map, which resulted in the identification of several candidate genes that might be underpinning the LB resistance in PI 270442. The identified QTL-linked markers can be used in breeding programs to transfer resistance from PI 270442 into the cultivated tomato via marker-assisted breeding and to develop near-isogenic lines for fine mapping of the QTLs.